Reflections of the potential role a narrative can play to enhance pedagogic efficacy - HANNAM, MR Fraser Douglas; LAURA, Professor Ronald Samuel (IJRDO- Journal of Educational Research, 2017)
Story telling in its most basic form is a means by which a culture passes onto the next generation what they have found to be useful, to be of value, or to be good. Curriculum can be understood as a certain way of telling a story about the world. By contextualising units of work within a narrative, lessons become more meaningful, dynamic and engaging for the learner. The burden of this paper will be explore the importance of narrative as a delivery system for reconceptualising the role of pedagogic strategies within the curriculum. Additionally, to unpack an emergent conceptualisation of the transformative potential of narrative for the storyteller.